Tunable optical bistability at the graphene-covered nonlinear interface - Xiang, Yuanjiang (2014)
We investigate theoretically the optical bistability of reflection at the interface between graphene and Kerr-type nonlinear substrates. We derive a simple procedure to calculate the nonlinear reflectivity with graphene, and discuss the influence of the graphene sheets on the hysteretic response of the TM-polarization reflected light. It is found that the bistable behavior of the reflected light can be electrically controlled via suitably varying the applied voltage on the graphene. In THz, the bistable thresholds can be lowered markedly by increasing the Fermi energy. However, in near-infrared frequency, it requires multiple graphene layers to exhibit significant influence on the bistable thresholds.